Research on residual strength characteristics of high water materials based on improved H-B criterion. - Lihui Zheng (Public Library of Science (PLoS), 2021)
To develop a new gangue polymer filling material with low compressive ratio, this paper intends to add high water cementing material to the gangue for backfilling. Uniaxial and tri-axial bearing experiments were conducted to study its bearing characteristics and residual strength. Based on Hock-Brown model theory, it is proposed that friction angle φr can be introduced to substitute model parameter mi, and the degree of cohesion loss can characterize the value of s. So the improved H-B model is established to characterize the residual strength of materials with ductile failure characteristics. The results show that the compressive strength of high water filling material increases linearly corresponding to the rise of confining pressure, and its strength characteristics conform to Mohr-Coulomb strength criterion. The ductile failure characteristics of the sample endow it with high residual strength, which in turn qualifies it for underground filling. After the introduction of cohesion and friction angle, the improved H-B criterion can fit the residual strength curve of the high water filling material more competently. The fitting coefficient of the samples with three water contents is 1.00, 0.99, and 1.00, respectively. The improved H-B model of residual strength demonstrates the change rule of residual strength of the samples corresponding to the change of confining pressure; under tri-axial loading, the angle between fracture surface and axial direction becomes larger as the confining pressure rises; and the failure mode of the material transforms from splitting failure to shear failure.